2023
DOI: 10.1002/adhm.202301984
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic Microenvironment Reconstruction with Synergistic Biofunctional Ions Promotes Diabetic Wound Healing

Xiaochen Chen,
Liyan Zhang,
Wenwen Chai
et al.

Abstract: Chronic hypoxia and ischemia make diabetic wounds non‐healing. Cellular functions of diabetic chronic wounds are inhibited under a pathological environment. Therefore, we developed a composite hydrogel system to promote diabetic wound healing. The composite hydrogel system consists of ε‐poly‐lysine, calcium peroxide, and borosilicate glass (BG). The hydrogel supplies continuous dissolved oxygen molecules to the wound that can penetrate the skin tissue to restore normal cellular function and promote vascular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…This demonstrates favorable in vitro biosafety (Figure S17). Previous studies have shown that certain inorganic metal ions, such as Zn 2+ , Fe 2+ , Cu 2+ , Ca 2+ , SiO 4 4– , and PO 4 3– , can enhance the migration of normal fibroblast cells, which is important for wound healing both in vitro and in vivo . To evaluate the impact of Zn-ASO NPs on mouse embryonic fibroblast cells (NIH-3T3) migration, we performed a scratch experiment. As shown in Figure A, all groups had similar wound widths at the initial time point.…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrates favorable in vitro biosafety (Figure S17). Previous studies have shown that certain inorganic metal ions, such as Zn 2+ , Fe 2+ , Cu 2+ , Ca 2+ , SiO 4 4– , and PO 4 3– , can enhance the migration of normal fibroblast cells, which is important for wound healing both in vitro and in vivo . To evaluate the impact of Zn-ASO NPs on mouse embryonic fibroblast cells (NIH-3T3) migration, we performed a scratch experiment. As shown in Figure A, all groups had similar wound widths at the initial time point.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al developed a pH‐responsive hydrogel based on a natural polymer loaded with insulin to be used as a bioactive dressing for enhancing diabetic wound healing 168 . Healing of foot ulcers of diabetic people is especially difficult, because of the acidic and hyperglycemic microenvironment 169 . A hydrogel was synthesized from n‐carboxyethyl chitosan ( N ‐chitosan), hyaluronic acid‐aldehyde (HA‐ALD), and adipic acid dihydrazide (ADH) with acyl hydrazone, a pH‐sensitive reversible dynamic bond.…”
Section: Non‐linear Functional Polymers Containing Cleavable Bondsmentioning
confidence: 99%